2017
DOI: 10.1159/000454717
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Neuroimaging Techniques in Pediatric Hydrocephalus

Abstract: From the early days of pneumoencephalography and ventriculography to the emerging technology of magnetic resonance diffusion tensor imaging (DTI) of the present day, neuroimaging has always been a critical tool in the diagnosis and treatment of pediatric hydrocephalus. There is accumulating evidence from both human and animal research suggesting that one of the major pathophysiological mechanisms underlying poor outcomes in these children is damage to vulnerable white matter (WM) structures in the brain as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…CT is also clinically useful for unstable patients or patients with implanted devices such as cochlear implants. 19 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…CT is also clinically useful for unstable patients or patients with implanted devices such as cochlear implants. 19 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…Diffusion tensor imaging studies have shown that disturbed periventricular white matter integrity is associated with neurobehavioral deficits in pediatric hydrocephalus [13,14] and that shunting gradually improves these deficits over time [15,16]. The reduction in myelination and capillary densities [17,18], as well as extracellular edema and macrophages [19,20] are documented in earlier studies in autopsies or cerebral biopsies performed in pediatric patients with severe hydrocephalus [21].…”
Section: Introductionmentioning
confidence: 98%
“…Pediatric hydrocephalus is a disease characterized by a complex set of neurological indications—in particular a high volume of cerebrospinal fluid in the cerebral ventricles. While there is interest in studying pediatric hydrocephalus using neuroimaging techniques to learn more about the disease, working with these images may prove to be difficult given the potentially large pathology induced deformations and artifacts from surgical treatment (e.g., shunts) ( Ou et al, 2014 ; Patel et al, 2017 ). When performing neuroimaging studies, a common goal is to be able to compare findings between participants.…”
Section: Introductionmentioning
confidence: 99%